2012
DOI: 10.1111/j.1365-2842.2012.02300.x
|View full text |Cite
|
Sign up to set email alerts
|

Occlusal dysesthesia: a qualitative systematic review of the epidemiology, aetiology and management

Abstract: Occlusal dysesthesia refers to a persistent complaint of uncomfortable bite sensation with no obvious occlusal discrepancy. This systematic review aimed to draw a picture of such patients, to present an agreement of previously reported diagnostic criteria and to analyse the evidence level of the recommended management approaches. An electronic search for all relevant reports on occlusal dysesthesia was thoroughly performed based on previous nomenclatures (e.g. phantom bite, occlusal hyperawareness) in PubMed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
65
0
6

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(73 citation statements)
references
References 21 publications
(68 reference statements)
2
65
0
6
Order By: Relevance
“…We found that PBS occurs predominantly in women and adults aged 30−70 years, with a peak in the 50s and 60s, supporting previous results [4].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We found that PBS occurs predominantly in women and adults aged 30−70 years, with a peak in the 50s and 60s, supporting previous results [4].…”
Section: Discussionsupporting
confidence: 92%
“…Phantom bite syndrome (PBS) [1] also termed occlusal discomfort [2], or occlusal dysesthesia [3,4], is characterized by a persistent uncomfortable sensation of occlusions without an evident occlusal discrepancy. Affected individuals complain that their occlusion is "wrong," "somewhat high/low," or "the bite is off."…”
Section: Introductionmentioning
confidence: 99%
“…The mean age of phantom bite patients is 51.744610.6 years, and the male/female ratio is 1 : 5.1. 3 Phantom bite patients report that their bite is off, meaning that they are unable to find a comfortable bite position. 4,5 These patients are preoccupied with their occlusion and constantly check their bites.…”
Section: Discussionmentioning
confidence: 99%
“…A recent systemic review of the literature provided the unified diagnostic criteria for phantom bite that is illustrated in Table 1. 3 A few etiological hypotheses for the symptoms of phantom bite have been provided. Marbach, 1 who was the first to coin the term ''phantom bite'' in 1976, proposed that schizophrenia, typically with paranoid features, underlies the condition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation